Correction: Experimental studies on the rheology of cubic blue phases. Issue 4 (15th December 2015) - Sahoo, Rasmita; Chojnowska, O.; Dabrowski, R.; Dhara, Surajit
Abstract : Correction for 'Experimental studies on the rheology of cubic blue phases' by Rasmita Sahoo et al., Soft Matter, 2016, DOI: ; Web:10.1039/c5sm02299a .